First principles study of nearly strain-free Ni/WSe2 and Ni/MoS2 interfaces. (12th August 2021) - Stollenwerk, Andrew J; Stuelke, Lukas; Margaryan, Lilit; Kidd, Timothy E; Lukashev, Pavel V
Abstract: Metal/transition metal dichalcogenide interfaces are the subject of active research, in part because they provide various possibilities for interplay of electronic and magnetic properties with potential device applications. Here, we present results of our first principles calculations of nearly strain-free Ni/WSe2 and Ni/MoS2 interfaces in thin-film geometry. It is shown that while both the WSe2 and MoS2 layers adjacent to Ni undergo metallic transition, the layers farther from the interface remain semiconducting. In addition, a moderate value of spin-polarization is induced on interfacial WSe2 and MoS2 layers. At the same time, the electronic and magnetic properties of Ni are nearly unaffected by the presence of WSe2 and MoS2, except a small reduction of magnetic moment at the interfacial Ni atoms. These results can be used as a reference for experimental efforts on epitaxial metal/transition metal dichalcogenide heterostructures, with potential application in modern magnetic storage devices.